Determination of CaCO3 Content in Egg Shell - Risani Rusnel, Azizah; Putri Karim, Dinda; Marlini, Rahmida; Maharani, Siska (Journal of Global Research Education, 2025)
The complexometry titration investigation has been conducting to ascertain the CaCO3 concentration of  Egg. The complex substance EDTA will hold the calcium, and the point will be signaled by a change in the metallochromic indicator's color. Standardization EDTA : Pipette 25 mL of MgSO4.7H2O solution, 10 mL of buffer solution pH 10, a little amount of  EBT indicator, and aqua DM into the titration flask. When you titrate with EDTA solution, the solution turns blue. Data processing has revealed that eggshell contains 0,025 grams of calcium and that the calcium content is 14,1%. Theoretically, eggshell is made up of crystals of CaCO3 (98,43%) based on the current mineral composition. Ca3(PO4)2 (0.75%) and MgCO3 (0.84%). Calcium carbonate is the main component of eggshell. When the titrant and titrate interact to create a complex molecule, the titration is known as a complexometric titration. A solution containing Ca2+ will form a complex with EDTA, according to the fundamental tenet of complexometry. CaCO3 was present in the sample (duck eggshell) in an amount of 0.025 grams, and a CaCO3 value of 15.7% was determined.